The Dead Sea Scrolls uncovered the first complete translation and interpretation of 50 key documents withheld for over 35 years - Eisenman, Robert H.; Wise, Michael Owen 1954- (Element, 1992)
"For the first time the public will be able to see the most interesting and exciting texts from the unpublished corpus and judge for itself. Providing precise English translations and complete transcriptions into modern Hebrew characters, The Dead Sea Scrolls Uncovered makes generally available in a clear and accessible style fifty of the best texts. Accompanied by incisive and readable commentaries aimed at both lay person and scholar alike, these texts provide exciting and ground-breaking insights into Messianism, an alternative presentation of the flood story, ecstatic visions, prophecies, Mysteries, astrology, divination, and much more." "This is nothing less than the literature of the Messianic Movement in Palestine. Responsible for the uprising that led to the destruction of the Temple in Jerusalem, its later stages are virtually indistinguishable from the rise of Christianity in Palestine. Professors Eisenman's and Wise's research will go a long way towards solving the problem of the Scrolls in the context of Jewish history of the period and shed new light on the formation of early Christianity."--BOOK JACKET
Keywords: Dead Sea scrolls. -- 4Q; Qumrantexte; Israel; Jordan; Manuscripts; Manuscrits de la mer Morte - 4Q; Manuscrits de la mer Morte - 4Q - Critique, interprétation, etc; Christianisme - Palestine - Origines - Ouvrages avant 1800; Dode-Zeerollen; Judaïsme - Ouvrages avant 1900; Messianisme juif - Ouvrages avant 1800; Geschichte